Role of Influencers in Propagating Abnormal Trends - Pallavi Dubey (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The advent of social media platforms has significantly empowered individuals to attain influencer status, wherein their reach and persuasive power shape public behavior, beliefs, and trends. While influencers often propagate benign or beneficial con-tent—ranging from lifestyle choices to health-related advice—there is a growing concern regarding their role in disseminating and normalizing “abnormal trends,” defined here as behaviors or practices that deviate from societal norms and may pose psychological, social, or physical risks. This study examines how influencers contribute to the propagation of such abnormal trends, exploring theoretical underpinnings from social learning theory and social comparison theory, delineating the mechanisms through which abnormal content spreads, and analyzing case studies of documented phenomena (e.g., self-harm challenges and dangerous pranks). Additionally, this paper discusses the psychological impact on vulnerable populations, ethical considerations for platform governance, and potential interventions. Through a synthesis of the extant literature, this study aims to provide a comprehensive understanding of influencers’ roles in abnormal trend proliferation and offers recommendations for researchers, policymakers, and platform administrators.